Protean Career Attitudes and Boundaryless Career Attitudes Can Predict Subjective Career Success in Teachers: [Protean Career Attitudes dan Boundaryless Career Attitudes Dapat Memprediksi Subjective Career Success Dalam Profesi Guru] - Ingarianti, Tri Muji; Gustiana, Ririn; Qoniah, Hanifatul; Andriany, Devina (ANIMA Indonesian Psychological Journal, 2023)
Teachers are foundational, and have great influence in the world of education. In their careers as teachers, these people must no longer care only about their own interests, but must also focus on the progress of the children they teach. The presence of this new concept in their careers can, it is thought, become an indicator for teachers in identifying and evaluating their careers, so that they may achieve career success, using subjective criteria. This study was aimed at understanding the roles of protean career attitudes (PCA) and boundaryless career attitudes (BCA) regarding the subjective career success of teachers. The approach in the study was a quantitative one, with the number of participants being 320 teachers, living in Java and Kalimantan. The instruments utilized were the Protean Career Attitudes Scale (PCAS), the Boundaryless Career Attitudes Scale (BCAS), and the Subjective Career Success Inventory (SCSI). Multiple regressive linear testing overall, and per dimension, produced scores in which p < .01, and indicated the existence of the roles of protean career attitudes (PCA) and boundaryless career attitudes (BCA) regarding the subjective career success of teachers, as well as the existence of the roles of each dimension of the study variables. Guru merupakan fondasi yang sangat berpengaruh dalam dunia pendidikan. Dalam karier sebagai guru, seharusnya guru tidak lagi hanya mempedulikan kepentingan untuk dirinya sendiri, namun juga berfokus pada kemajuan anak didik. Keberadaaan konsep baru dalam karier diduga dapat menjadi indikator untuk guru dalam mengenali dan mengevaluasi kariernya, sehingga dapat mencapai kesuksesan karier menggunakan kriteria subjektif. Studi ini bertujuan untuk mengetahui peran dari protean career attitudes (PCA) dan boundaryless career attitudes (BCA) terhadap subjective career success pada guru. Pendekatan dalam studi ini adalah pendekatan kuantitatif dengan jumlah partisipan sebanyak 320 guru yang berdomisili di Jawa dan Kalimantan. Instrumen yang digunakan adalah Protean Career Attitudes Scale (PCAS), Boundaryless Career Attitudes Scale (BCAS), dan Subjective Career Success Inventory (SCSI). Uji regresi linier berganda secara menyeluruh dan per dimensi menghasilkan skor dengan p < 0,01, yang menunjukkan adanya peran protean career attitudes (PCA) dan boundaryless career attitudes (BCA) terhadap subjective career success pada guru, serta adanya peran tiap dimensi dari variabel studi.